Faktor Yang Mempengaruhi Kelulusan Uji Kompetensi Ners di Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia - Massi, Siti Hardianty; Sri Asnaniar, Wa Ode; Agustini, Tutik (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Competence test is evaluation of learning and it can be used as a measure of success and problem that often faced and to test the ability of nurse whether they are competent or not. Objective to determine the effect of health, motivation, preparation, grade point average of S1 and ners toward the passing of competence test in public health of muslim university of Indonesia. Methods of this research uses cross sectional analytic with quantitative approach. For determining the sample done with accidental sampling with a large sample of 210 respondents.Results it was found that there was not health effect with the passing of the nurse competence test (p=0,125), and there is an influences of motivation (p=0,000), preparation (p=0,000), grade point average of S1 (p=0,000), Ners (p=0,000) with the nursing competence test.Conclusion of this research is only motivation, preparation, grade point average of S1 and ners have any influence with nurse competence test. Option in health has not influence with the graduation of nurse competence test in public health faculty of muslim university of Indonesia. Therefore, it is expected that students of the professional nurses program can optimize about their academic self-regulation. As well as physical condition related to health in taking the competence test, there are who support it will get competent result.